IMMUNOGENICITY AND PROTECTIVITY OF THE OUTER MEMBRANE PROTEIN BANDS OF PASTEURELLA MULTOCIDA ISOLATE U-6 - Ignatius Mulyadi; Widya Asmara; B. Sardjono (Jurnal Sain Veteriner, 1998)
The most immunogenic and protective fraction of outer membrane proteins of Pasieurella multacida has not well understood. This study was done to find our the immunogenicity and protectivity of outer membrane protein fractions of Pasteurella multicida isolat U-6 in mice. The organism was cultured in Luria Bertani broth. The outer membrane proteins were prepared according 10 Snipes et al., (1988), Electrophoresis of the protein was carried out in 10% of sodium dodecy 1-su I ph ale poly cry 1 amide gel electrophoresis, and stained with 0.3% Coomasie brilliant blue. The result indicated that there arc many protein bands with 5 major protein bands, those are having molecular weight of 20,1 kilo Dalton (kD), 27 kD, 36 kD, 52,7kD,and75 kD. Each protein bandof molecular weight of 27 kD, 36kD,and75kD was then cut, and homogenised, and was used as antigen to immunise the mice after added with adjuvant 1:1. Two weeks after immunisation all of the mice were bled and the sera were tested by ELISA. FourtyeigM hours from bleeding, ail of the immunised and control mice were challenged with 500 colony forming unit of virulent Pasteurefla mutticida isolate U-6, and observed their mortality. The result indicated thai the outer membrane protein bands of molecular weight of 36 kD and 75 kD were immunogenic (P>0,05), while the outer membrane protein band of 27 kD was less immunogenic (P>0.05), Band with moleculer weight of 27 kD produced 0% protection, bandof 36 kD produced 60% protection, and band of 75 kD produced 40% protection of mice challenged.